Combustion efficiency in a fluidized-bed combustor with a modified perforated plate for air distribution - Erdiwansyah, .; Mahidin, .; Husni, Husin; Nasaruddin, .; Muhtadin, .; Muhammad, Faisal; Asri, Gani; Usman, .; R., Mamat (MDPI AG, 2021)
Combustion efficiency is one of the most important parameters especially in the fluidized-bed combustor. Investigations into the efficiency of combustion in fluidized-bed combustor fuels using solid biomass waste fuels in recent years are increasingly in demand by researchers around the world. Specifically, this study aims to calculate the combustion efficiency in the fluidized-bed combustor. Combustion efficiency is calculated based on combustion results from the modification of hollow plates in the fluidized-bed combustor. The modified hollow plate aims to control combustion so that the fuel incorporated can burn out and not saturate. The combustion experiments were tested using palm oil biomass solid waste fuels such as palm kernel shell, oil palm midrib, and empty fruit bunches. The results of the measurements showed that the maximum combustion temperature for the palm kernel shell fuel reached 863 °C for M1 and 887 °C for M2. The maximum combustion temperature measurements for M1 and M2 from the oil palm midrib fuel testing reached 898 °C and 858 °C, respectively, while the maximum combustion temperature for M1 and M2 from the empty fruit bunches fuel was 667 °C and M2 847 °C, respectively. The rate of combustion efficiency with the modification of the hole plate in the fluidized-bed combustor reached 96.2%. Thermal efficiency in fluidized-bed combustors for oil palm midrib was 72.62%, for PKS was 70.03%, and for empty fruit bunches was 52.43%. The highest heat transfer rates for the oil palm midrib fuel reached 7792.36 W/m2, palm kernel shell 7167.38 W/m2, and empty fruit bunches 5127.83 W/m2. Thus, the modification of the holed plate in the fluidized-bed combustor chamber showed better performance of the plate than without modification.